DIFFERENCES BETWEEN AUDIT QUALITY PROVIDED BY INTERNATIONAL AND LOCAL AUDIT FIRMS: THE RESEARCH ON AUDIT CLIENTS’ PERCEPTIONS IN THE AUDIT MARKET OF LITHUANIA - Vaicekauskas, Darius (Ekonomika, 2015)
The article investigates the quality of audit services that international and local (operating nationally) audit firms are offering. There has been a great amount of effort put in recent years to improve audit quality due to the increase of auditing scandals in various corporations across the world. To improve audit quality, it is crucial to assure that all the stakeholders of the auditing triangular relationship would be satisfied with the outcomes (what is provided) and the process (how the service is provided) of audit services. Considerable attention should be paid not only to the external users (third-parties), but also to the audit clients as their perceptions of what is a quality audit are very subjective.In the last couple of decades, there has been a lot of effort put into research whether the best international audit firms do actually provide audits of higher quality than the local audit firms that are based nationally. The main criterion that these firms are compared in a vast body of literature is the accuracy of the information that was provided to the third parties in auditors’ reports, i.e. in many studies the correct auditor’s report is used as a proxy for audit quality.The aim of this study was to investigate whether Lithuanian audit clients perceive audit services to be better in quality when employing local or international audit firms. This paper will theoretically discuss the audit quality differences between international and local audit firms, and it will present the results of the survey of Lithuanian audit clients.The survey used the questionnaire based on 12 audit quality criteria assessible for the client. The criteria represented audit service’s value added and the performance, i.e. how the audit was conducted. Results of the survey imply that both international and local audit firms provide their clients with the same level of added value and audit performance, except the following significant differences. It can be stated that Lithuanian audit clients perceive audit provided by local audit firms to be of a higher quality than those provided by international audit firms in terms of the insights on tax risks (value added criterion), partner’s involvement in their audit, and perceived competence of audit assistants (audit performance criteria).
Keywords: audit quality; international audit firms; local audit firms; audit clients